Compliance with standard precautions by nursing professionals in high complexity care - Daniela Rosa Floriano; Luana Silva Rodrigues; Cintia Machado Dutra; Silmara Elaine Malaguti Toffano; Fernanda Maria Vieira Pereira; Suzel Regina Ribeiro Chavaglia (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: To evaluate the compliance with Standard Precautions by nursing professionals from high complexity units. Methods: Quantitative, descriptive and cross-sectional study, carried out in a Brazilian public hospital between January and March 2017. Data collection was performed through the application of an instrument with demographic and professional variables and the Brazilian version of Compliance with Standard Precautions Scale (CSPS-PB). Data were analyzed using descriptive and inferential statistics with IBM SPSS® software. Results: A total of 148 professionals participated. The rate of compliance with SP was 65.0%. There was a statistically significant difference only in relation to the professional category (p<0.001). Conclusion and implications for practice: Compliance with SP by nursing professionals was lower than expected and there was association of compliance with SP mean scores only for professional category. These results may contribute to direct strategies to encourage adherence to SP, improving the safety of professionals and patients.